Verification of test of antagonistic muscle groups cooperation - Tesarova, K.; Bezdekova, D.; Vaverka, F.; Novotny, J. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Manipulation activities pertain to movement manifestations of the upper limbs into target position within a given range. The preciseness of quality of the performed movement depends on the level of cooperation extended by antagonistic muscle groups under control of the central nervous system. A number of studies have been published on the field of motor control dealing with analysis of movement in one joint with one degree of freedom (Zelaznik, 1996; Jaric et al., 2000). The aim of this study is to verify reliability of the test of cooperation of antagonistic muscle groups in a simple forearm movement.